Features of the use of mathematical statistical methods in the process of pedagogical research - Tosmathova Ormonoy Rakhimovna (Research Parks Publishing LLC, 2021)
The article activates the problem of the necessary application of mathematical statistical methods in a broad sense in the practical part of pedagogical research activities. Accordingly, it is necessary to determine the role and importance of mathematical statistics in pedagogical research, and on this basis it is necessary to organize the methodology of using mathematical statistics, as increasing the quality and practical significance of pedagogical research results, increasing the requirements for pedagogical research as a basis for the problems of finding statistical methods that meet these requirements are described in detail